Determinan Penghasilan Utama pada Sektor Kehutanan di Indonesia - Dedharya Immanuella Wardjanan; Atika Fatimah (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
The forestry sector directly and indirectly makes a significant contribution to Indonesia's GDP. Forestry sector income is obtained from wood extraction activities, the wood processing industry, as well as related service sectors such as forest tourism and ecotourism. However, in 2021, the percentage contribution of the forestry sector to GDP is 0.66% or the lowest during 2017-2021, even lower than in 2020 when Covid-19 was occurring. This research aims to analyze the factors that influence the main income in the forestry sector in Indonesia. The data collection method is documentation and the data analysis method uses multiple linear regression. The data used in this research is cross section data from 34 provinces during 2021. The results of this research are that the variables of forestry plant cultivation labor and forest product levy labor have a significant effect on the main income of the forestry sector. Meanwhile, the mangrove ecosystem variable does not have a significant effect on the main income of the forestry sector. This is because more than half of the mangrove forest ecosystem in Indonesia is in a seriously damaged condition.